Pengaruh Sistem Informasi Akuntansi Dan Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Pemerintahan Desa Pada Tingkat Kecamatan Palue - Novita Novita; Maria Nona Dince; Konstantinus Pati Sanga (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to determine the influence of accounting information systems and internal control systems on the quality of village government financial reports at the Palue District level. This type of research is quantitative research. The data collection method in this study used a questionnaire. The population in this study were village officials in Palue District, where the number of samples was 56 respondents. The tests used are research instrument tests, descriptive statistical analysis, classical assumption tests, hypothesis tests, multiple linear regression analysis and model feasibility tests using SPSS 16 tools. Based on the results of the t test and F test partially or simultaneously the accounting information system and system internal control affects the quality of village government financial reports in Palue District.